2022
DOI: 10.1108/acmm-08-2021-2532
|View full text |Cite
|
Sign up to set email alerts
|

Modification and corrosion resistance of halloysite carrier with metal nanoinhibitor in marine corrosion environment

Abstract: Purpose The purpose of this paper is to provide theoretical guidance and an experimental basis for a smart anti-corrosion coating of halloysite nanocontainers loaded with benzotriazole (BTA) inhibitors on copper in a marine corrosion environment. Design/methodology/approach In the present study, the smart anti-corrosion coatings of halloysite nanocontainers loaded inhibitors on copper were synthesized by adding BTA inside the halloysite nanocontainers. Then, the halloysite carrier’s surface topography and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Furthermore, the exemplary characteristics of one-dimensional CNTs, characterized by a hollow tubular structure, including a vast specific area, a high aspect ratio and excellent thermal and chemical stability, make them ideal for various organic coating applications. Additionally, halloysite nanotubes (HNTs), with their hollow tubular structure, high aspect ratio, natural abundance and versatile functionality, hold significant benefits for loading corrosion inhibitors (Wang et al, 2022;Liu et al, 2022b). They are capable of absorbing inhibitors within their interior pores.…”
Section: Methods To Prepare the Polyanilinementioning
confidence: 99%
“…Furthermore, the exemplary characteristics of one-dimensional CNTs, characterized by a hollow tubular structure, including a vast specific area, a high aspect ratio and excellent thermal and chemical stability, make them ideal for various organic coating applications. Additionally, halloysite nanotubes (HNTs), with their hollow tubular structure, high aspect ratio, natural abundance and versatile functionality, hold significant benefits for loading corrosion inhibitors (Wang et al, 2022;Liu et al, 2022b). They are capable of absorbing inhibitors within their interior pores.…”
Section: Methods To Prepare the Polyanilinementioning
confidence: 99%
“…BTA is the specific corrosion inhibitor for copper and its alloy. It is also reported that BTA has corrosion inhibition effect for Al alloy and carbon steel (Ren et al , 2022; Petrunin et al , 2020; Wang et al , 2022).…”
Section: Introductionmentioning
confidence: 92%
“…Such as silica (Liu et al , 2022; Nguyen et al , 2022), carbon nanotubes, halloysite (HNTs), graphene and montmorillonite (Xing et al , 2018a, 2018b; Matangouo et al , 2021), which have great potential as nanocarriers for continuous drug delivery. HNTs have become one of the most widely used drug nanocarriers because of their low price and good biocompatibility (Barman et al , 2020; Wang et al , 2022). The molecular structure of HNTs is Al 2 O 3 ·2SiO 2 ·4H 2 O.…”
Section: Introductionmentioning
confidence: 99%